The echo wife - Gailey, Sarah (New York : Tor, 2021)
"Evelyn Caldwell's husband Nathan has been having an affair - with Evelyn Caldwell. Or, to be exact, with a genetically cloned replica."--
"A Tom Doherty Associates book."
Keywords: Human cloning -- Fiction; Husband and wife -- Fiction; Adultery -- Fiction; Murder -- Fiction; Science fiction; Thrillers (Fiction)